Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\sqrt{32}\cdot18+2\cdot\sqrt{25}+\left|\frac{-1}{3}\right|\cdot\left|-6\right|-2^2\)
\(=4\cdot\sqrt{2}\cdot18+2\cdot5+\frac{1}{3}\cdot6-4\)
\(=72\cdot\sqrt{2}+\left(10+2-4\right)\)
\(=72\cdot\sqrt{2}+8\)
\(=8+72\sqrt{2}\)
\(\left(x^2-4\right)\cdot\sqrt{x}=0\)
\(\Rightarrow\orbr{\begin{cases}\left(x^2-4\right)=0\\\sqrt{x}=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x^2=0+4\\x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x^2=4\\x=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=-2\\x=2\\x=0\end{cases}}\)
a) Đặt A=\(\frac{x^2-1}{x^2}\)
Ta có:
\(\Rightarrow A=\frac{x^2}{x^2}-\frac{1}{x^2}\)
\(\Rightarrow A=1-\frac{1}{x^2}\)
\(\Rightarrow x\in Z\) để thỏa mãn A<0
b)\(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\)
=>(a^2+b^2)*cd=(c^2+d^2)*ab
a^2cd+b^2cd=abc^c+abd^2
a^2cd+b^2cd-c^2ab-d^2ab=0
(a^2cd-abd^2+(b^2cd-abc^2)=0
ad(ac-bd)-bc(ac-bd)=0
(ad-bc)(ac-bd)=0
=>ad-bc=0 hoặc ac-bd=0
ad=bc ac=bd
=>a/b=c/d hoặc a/d=b/c
Bai 1
a) \(\sqrt{0,36}+\sqrt{0,49}=0,6+0,7=1,3\)
b) \(\sqrt{\frac{4}{9}}-\sqrt{\frac{25}{36}}=\frac{2}{3}-\frac{5}{6}\)
=\(-\frac{1}{6}\)
Bài 2
a)\(x^2=81\Rightarrow\left[{}\begin{matrix}x=9\\x=-9\end{matrix}\right.\)
b) \(\left(x-1\right)^2=\frac{9}{16}\)
\(\Rightarrow\left[{}\begin{matrix}x-1=\frac{3}{4}\\x-1=\frac{-3}{4}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\frac{7}{4}\\x=\frac{1}{4}\end{matrix}\right.\)
c) \(x-2\sqrt{x}=0\Rightarrow\sqrt{x}\left(\sqrt{x}-2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}\sqrt{x}=0\\\sqrt{x}-2=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=4\end{matrix}\right.\)
d) \(x=\sqrt{x}\Rightarrow x-\sqrt{x}=0\Rightarrow\sqrt{x}\left(\sqrt{x}-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}\sqrt{x}=0\\\sqrt{x}-1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)